African economy: the ceramic evidence - (:unkn) unknown (My University, 2022)
Ceramic evidence is one of the main sources of study for the economy of Roman Africa. This is partly a consequence of the lack of direct archaeological evidence for foodstuff production in this region (although presses have been studied, only two farms have recently been excavated, in Tunisia, and only one in Libya), and more importantly on account of the wide distribution of African pottery (amphorae, tableware, cooking ware, lamps) throughout the Empire and sometimes beyond. There have, nonetheless, been a number of important studies over the last forty-five years which have attempted to integrate the limited archaeological information on African agriculture with the abundant, if equivocal, evidence of pottery. In this chapter the author will focus chiefly on the importance of pottery as an indicator of production and performance in the Roman economy, in particular its relationship with territories, foodstuffs and trade, as well as some of the recurring problems in the study of African wares.
Keywords: African Research